Association of Circulating Follicular Helper T Cells and Serum CXCL13 With Neuromyelitis Optica Spectrum Disorders - Yang, Xiaoyan; Peng, Jing; Huang, Xiaoxi; Liu, Peidong; Li, Juan; Pan, Jiali; Wei, Zhihua; Liu, Ju; Chen, Min; Liu, Hongbo (Frontiers in Immunology, 2021)
Background: Neuromyelitis optica spectrum disorders (NMOSDs) are severe inflammatory diseases mediated mainly by humoral and cellular immunity. Circulating follicular helper T (Tfh) cells are thought to be involved in the pathogenesis of NMOSD, and serum C-X-C motif ligand 13 (CXCL13) levels reflect the effects of Tfh cells on B-cell-mediated humoralimmunity. Immune cell and cytokine changes during the dynamic relapsing and remitting processes in NMOSD require further exploration. Patients and methods: Blood samples were collected from 36 patients in acute and recovery phases of NMOSD, 20 patients with other noninflammatory neurological diseases (ONND) and 20 age- and sex-matched healthy volunteers. CD4+CXCR5+PD-1+ Tfh cells were detected by flow cytometry, and serum CXCL13 levels were assessed by enzyme-linked immunosorbent assay (ELISA). Results: The percentage of CD4+CXCR5+PD-1+ Tfh cells was significantly higher during the acute phase than during the recovery phase, and serum CXCL13 levels were significantly higher in patients in the acute and recovery phases of NMOSD than in the ONND and control groups. The Tfh cell percentage was positively correlated with CXCL13 levels, and both were positively correlated with Expanded Disability Status Scale (EDSS) scores and cerebrospinal fluid protein levels in patients with acute NMOSD. Conclusion: Circulating Tfh cells level has the potential to be a biomarker of disease severity